Broadband High‐Responsivity Photodetectors Based on Large‐Scale Topological Crystalline Insulator SnTe Ultrathin Film Grown by Molecular Beam Epitaxy. Issue 5 (28th December 2016) - Jiang, Tian; Zang, Yunyi; Sun, Honghui; Zheng, Xin; Liu, Yu; Gong, Yan; Fang, Liang; Cheng, Xiang'ai; He, Ke
Abstract : SnTe is a kind of topological crystalline insulator (TCI) that possesses spin‐polarized, Dirac‐dispersive surface states protected by crystal symmetry, unlike topological insulators (TIs) with time‐reversal symmetry. TCIs can also exhibit a wide range of physical properties such as magnetism, superconductivity, and ferromagnetism, which are tunable by doping, straining, and alloying. Despite great progress in the synthesis and applications of TCIs, it remains a considerable challenge to prepare large‐scale ultrathin TCI films with high quality. Here, we report a controllable approach for the production of wafer‐scale SnTe thin films (5 mm × 2 mm) by molecular beam epitaxy (MBE). A highly efficient photoconductive detector based on the as‐prepared SnTe films features a fast and stable photoresponse from the visible to the mid‐infrared range (405 nm–3.8 µm). Moreover, the photodetector shows a relatively high responsivity (3.75 AW −1 at 2003 nm at room temperature). These results give a guideline for studying the intrinsic properties of TCIs and optimizing these devices for broadband and sensitive optoelectronic applications. Abstract : Broadband high‐responsivity photodetectors are fabricated by a simple molecular beam epitaxy process from SnTe ultrathin films. The photoconductive detectors exhibit a fast and stable photoresponse from the visible to the mid‐infrared range (405 nm–3.8 µm) with a relatively high responsivity (3.75 AW −1 at 2003 nm and room temperature), which will promote the applications of broadband and sensitive optoelectronic devices.